Can Clinical Simulation Increase Confidence Levels in Performing Postpartum Care in a Diverse Group of Baccalaureate Nursing Students?. Issue 2 (March 2018) - Germain, Michelle; O'Leary-Kelley, Colleen; Goyal, Deepika; Anand, Sulekha
Abstract : Abstract: Nursing duties are often sensitive in nature and may contribute to feelings of inadequacy for students, especially when providing postpartum care. Our study assessed confidence levels among 61 junior baccalaureate nursing students before and after a simulation workshop with a follow-up survey administered after completion of two full clinical days on a postpartum unit. The four-hour simulation included stations for breast, fundus, and lochia exam skills. Overall confidence and confidence in performing patient assessments were significantly increased at postsimulation and follow-up ( p < .001), demonstrating the efficacy of the simulation.